Isu-Isu Kontemporer Keagamaan : Islam dan Globalisasi - Elmen Sakup; Nikendro Nikendro; Agus Rifki Ridwan (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Contemporary religious issues in the context of Islam and globalization reflect the challenges and opportunities facing Muslims in the modern era. Globalization, as a process that connects various countries through technology, economics and culture, influences religious dynamics in various aspects. On the one hand, globalization paves the way for the spread of Islamic information and values ​​throughout the world, strengthening and how the Muslim community adapts to these dynamics through religious identity at the global level. On the other hand, globalization also raises concerns regarding the rise of secularism, individualism and consumerist culture which can threaten traditional Islamic values. Issues such as religious pluralism, human rights, feminism, and Islamic moderation are part of important discussions regarding Islamic responses to the challenges of globalization. Muslims are required to navigate between maintaining religious identity while engaging constructively in an increasingly connected world. This article aims to analyze various contemporary religious issues that have emerged in the midst of the globalization process, a contextual approach that prioritizes Islamic values ​​that are relevant in this global era.